Association Between Immunoglobulin G N-glycosylation and Vascular Cognitive Impairment in a Sample With Atherosclerosis: A Case-Control Study - Wang, Meng; Chen, Xueyu; Tang, Zhaoyang; Zhang, Wenran; Hou, Haifeng; Sun, Xiangfu; Shi, Yuqing; Lu, Xinxia; Li, Peirui; Ji, Long; Ding, Guoyong; Li, Dong (Frontiers in Aging Neuroscience, 2022)
Background: Atherosclerosis is considered a crucial component in the pathogenesis of decreased cognitive function, as occurs in VCI. Inflammation and the immune response play a significant role in the development of many chronic diseases. IgG N-glycosylation has been implicated in the development of a variety of diseases by affecting the anti-inflammatory and proinflammatory responses of IgG. This study aimed to investigate the association between IgG N-glycosylation and VCI in a sample of patients with atherosclerosis through a case-control study. Method: We recruited a total of 330 patients with atherosclerosis to participate in this case-control study, including 165 VCI patients and 165 sex- and age-matched participants with normal cognitive function. The plasma IgG N-glycans of participants were separated by ultrahigh-performance liquid chromatography. An ELISA kit was used to determine the corresponding serum inflammatory factors. Atherosclerosis was diagnosed by carotid ultrasound, and the diagnosis of VCI was based on the "Guidelines for the Diagnosis and Treatment of Vascular Cognitive Impairment in China (2019)". A multivariate logistic regression model was used to explore the association between IgG N-glycans and VCI. We also analysed the relationship between IgG N-glycans and the inflammatory state of VCI through canonical correlation analysis (CCA). Results: Through the multivariate logistic regression analysis, 8 glycans and 13 derived traits reflecting decreased sialylation and galactosylation and increased bisecting GlcNAc significantly differed between the case and control groups after adjusting for confounding factors (P<0.05, q<0.05). Similarly, the differences in TNF-α, IL-6, and IL-10 were statistically significant between the case and control groups after adjusting for the effects of confounding factors (P<0.05, q<0.05). The CCA results showed that VCI-related initial N-glycans were significantly correlated with VCI-related inflammatory factors (r=0.272, P=0.004). The combined AUC value (AUCcombined =0.885) of 7 initial glycans and inflammatory factors was higher than their respective values (AUCinitial glycans=0.818, AUCinflammatory factors=0.773). Conclusion: The findings indicate that decreased sialylation and galactosylation and increased bisecting GlcNAc reflected by IgG N-glycans might affect the occurrence of VCI in patients with atherosclerosis though promoting the proinflammatory function of IgG. IgG N-glycans may serve as potential biomarkers to distinguish VCI in individuals with atherosclerosis.